A composite adhesive and its application in battery sealing or assembly
By developing a composite adhesive containing room temperature vulcanized methyl silicone rubber, butyl rubber and modified filler, the problem of unsatisfactory tensile strength at low temperature in the prior art is solved, and a better pulling at low temperature is achieved The effect of stretch strength is suitable for sealing and assembly of power batteries.
Patent Information
- Application Number
- CN202310337086.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-03-31
AI Technical Summary
In the prior art, the tensile strength of graphene fire-resistant flame-retardant sealant at low temperature is not ideal, and it is difficult to meet the performance requirements of power batteries at low temperatures.
Develop a composite adhesive that contains room temperature vulcanized methyl silicone rubber, butyl rubber, modified filler and curing agent. The modified filler is prepared by modifying the concave and convex rod soil and wollastonite to significantly improve the composite bonding Tensile strength of the agent at low temperature.
The composite adhesive has good tensile strength at low temperatures, which can significantly improve the sealing and assembly performance of power batteries, and meet the needs of power batteries at low temperatures.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive preparation, and in particular to a composite adhesive and application thereof in battery sealing or assembly. Background Art
[0002] With the development of new energy vehicles in recent years, their share in the automotive industry has been increasing; and as an important component of new energy vehicles, the demand for power batteries has also been increasing. There are many production links for power batteries, among which the sealing and assembly of power batteries is one of the production links of power batteries, which also has a certain impact on the performance of power batteries. In the sealing and assembly of power batteries, adhesives are one of the commonly used materials, and the demand is also gradually increasing.
[0003] Chinese invention patent 202011098491.X discloses a graphene fire-retardant sealant, which discloses a graphene fire-retardant sealant. The graphene fire-retardant sealant comprises a fire-retardant sealant base material, and the fire-retardant sealant base material comprises room temperature vulcanized methyl silicone rubber, dimethyl silicone oil, flame retardant and heat-insulating agent A, and flame retardant and heat-insulating agent B; the flame retardant and heat-insulating agent A comprises active nano-calcium and aluminum hydroxide; the flame retardant and heat-insulating agent B comprises fumed silica, graphene and aerogel. The fire-retardant sealant provided by the present invention has good flame retardant and heat-insulating properties, a long service life, good elongation and strong anti-displacement ability. The inventor found in the study that the sealant disclosed in Chinese invention patent 202011098491.X has unsatisfactory tensile strength at low temperatures, which is difficult to meet the performance requirements of power batteries at low temperatures.
[0004] In summary, it is of great application value to develop a composite adhesive with good tensile strength at low temperature using room temperature vulcanized methyl silicone rubber as raw material. Summary of the invention
[0005] In order to overcome at least one of the technical problems existing in the prior art, the present invention provides a composite adhesive and application thereof in battery sealing or assembly.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] A composite adhesive comprises the following raw material components in parts by weight:
[0008] Room temperature vulcanized methyl silicone rubber 40-60 parts; butyl rubber 20-40 parts; filler 30-50 parts; curing agent 10-20 parts; coupling agent 1-5 parts;
[0009] The filler comprises attapulgite and wollastonite.
[0010] The invention provides a composite adhesive with a completely new composition; research shows that the composite adhesive has good tensile strength at low temperatures.
[0011] Preferably, the composite adhesive comprises the following raw material components in parts by weight:
[0012] Room temperature vulcanized methyl silicone rubber 50-60 parts; butyl rubber 30-40 parts; filler 40-50 parts; curing agent 10-15 parts; coupling agent 1-3 parts.
[0013] Most preferably, the composite adhesive comprises the following raw material components in parts by weight:
[0014] Room temperature vulcanized methyl silicone rubber 50 parts; butyl rubber 30 parts; filler 40 parts; curing agent 12 parts; coupling agent 3 parts.
[0015] Preferably, the weight ratio of attapulgite to wollastonite is 2 to 4:1.
[0016] Most preferably, the weight ratio of attapulgite to wollastonite is 3:1.
[0017] Preferably, the curing agent is selected from diethylaminomethyltriethoxysilane.
[0018] The coupling agent is selected from silane coupling agent KH-560.
[0019] Preferably, the filler is a modified filler; the modified filler is prepared by the following method:
[0020] (1) mixing attapulgite and wollastonite, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion;
[0021] (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 40 to 60° C. for 1 to 3 hours. After the stirring is completed, the solid is taken out and dried to obtain a solid product 1;
[0022] (3) calcining the solid product 1 at 700-800° C. for 2-4 hours to obtain a solid product 2, i.e., the modified filler.
[0023] The inventors surprisingly found in a large number of studies that the composite adhesive prepared by adding modified fillers obtained by modifying attapulgite and wollastonite by the above method to room temperature vulcanized methyl silicone rubber and butyl rubber can significantly improve the tensile strength of the composite adhesive at low temperatures, compared with the composite adhesive prepared by adding unmodified fillers composed of attapulgite and wollastonite.
[0024] Preferably, in step (1), the weight ratio of the total weight of attapulgite and wollastonite to water is 1:8-10.
[0025] Most preferably, the weight ratio of the total weight of attapulgite and wollastonite to water is 1:9.
[0026] Preferably, the weight ratio of attapulgite to wollastonite in step (1) is 2 to 4:1.
[0027] Most preferably, the weight ratio of attapulgite to wollastonite is 3:1.
[0028] Preferably, in step (2), the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and dispersion is: 4-6:1-2:1-2:400-600.
[0029] Most preferably, the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and dispersion in step (2) is 5:2:1:500.
[0030] Preferably, the method for preparing the modified filler further comprises the following steps:
[0031] The solid product 2 is dispersed in water, and then a modifier is added, and stirring is continued at 60 to 90° C. for 1 to 3 hours. The solid product is separated and dried to obtain the modified filler.
[0032] The inventors surprisingly found in further research that in the preparation process of the modified filler, the modified filler obtained by further modifying the solid product 2 by adding a modifier can further improve the tensile strength of the prepared composite adhesive at low temperature.
[0033] Further preferably, the weight ratio of the solid product 2, the modifier and the water is 8-12:2-4:100;
[0034] Further preferably, the weight ratio of the solid product 2, the modifier and the water is 10:3:100.
[0035] More preferably, the modifier is selected from myristyltrimethylammonium chloride, tetradecyldimethylbenzylammonium chloride or didecyldimethylammonium chloride.
[0036] More preferably, the modifier consists of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride.
[0037] Further preferably, the weight ratio of tetradecyl dimethyl benzyl ammonium chloride to didecyl dimethyl ammonium chloride is 1-2:1-2;
[0038] Most preferably, the weight ratio of tetradecyldimethylbenzyl ammonium chloride to didecyldimethylammonium chloride is 1:1.
[0039] The inventors also found in the study that the selection of modifiers has an important influence on the tensile strength of the prepared composite adhesive at low temperatures; the inventors surprisingly found in a large number of experiments that when the modifier is selected from a composite modifier consisting of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride, the tensile strength of the prepared composite adhesive at low temperatures can be synergistically improved; the degree of improvement in the tensile strength of the prepared composite adhesive at low temperatures is much higher than that of the composite adhesive prepared by the modifier being selected from a single myristyl trimethyl ammonium chloride, tetradecyl dimethyl benzyl ammonium chloride or didecyl dimethyl ammonium chloride; and also much higher than that of the composite adhesive prepared by the modifier being selected from a composite modifier consisting of myristyl trimethyl ammonium chloride and tetradecyl dimethyl benzyl ammonium chloride, or the modifier being selected from a composite modifier consisting of myristyl trimethyl ammonium chloride and didecyl dimethyl ammonium chloride.
[0040] Beneficial effects: The present invention provides a composite adhesive with a new composition; studies have shown that it has good tensile strength at low temperatures. In particular, the composite adhesive contains a modified filler obtained by modifying attapulgite and wollastonite according to the method of the present invention, which can significantly improve the tensile strength of the composite adhesive at low temperatures compared to the composite adhesive containing unmodified fillers composed of attapulgite and wollastonite. DETAILED DESCRIPTION
[0041] The present invention is further explained below in conjunction with specific examples, but the examples do not limit the present invention in any form.
[0042] Example 1 Preparation of composite adhesive
[0043] The raw materials are composed by weight: 50 parts of room temperature vulcanized methyl silicone rubber; 30 parts of butyl rubber; 40 parts of filler; 12 parts of curing agent (specifically diethylaminomethyltriethoxysilane); 3 parts of coupling agent (specifically silane coupling agent KH-560);
[0044] The filler is composed of attapulgite and wollastonite in a weight ratio of 3:1.
[0045] Preparation method: Evenly mix room temperature vulcanized methyl silicone rubber, butyl rubber, filler, curing agent and coupling agent to obtain the composite adhesive.
[0046] Example 2 Preparation of composite adhesive
[0047] The raw materials are composed by weight: 50 parts of room temperature vulcanized methyl silicone rubber; 30 parts of butyl rubber; 40 parts of modified filler; 12 parts of curing agent (specifically diethylaminomethyltriethoxysilane); 3 parts of coupling agent (specifically silane coupling agent KH-560);
[0048] The modified filler is prepared by the following method:
[0049] (1) mixing attapulgite and wollastonite in a weight ratio of 3:1, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion; wherein the weight ratio of the total weight of the attapulgite and wollastonite to the weight of water is 1:9;
[0050] (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 50° C. for 2 h. After the stirring is completed, taking the solid and drying it to obtain a solid product 1; wherein the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and the dispersion is 5:2:1:500;
[0051] (3) The solid product 1 was calcined at 750° C. for 3 h to obtain a solid product 2, i.e., the modified filler.
[0052] Preparation method: room temperature vulcanized methyl silicone rubber, butyl rubber, modified filler, curing agent and coupling agent are uniformly mixed to obtain the composite adhesive.
[0053] Example 3 Preparation of composite adhesive
[0054] Raw materials are composed by weight: 60 parts of room temperature vulcanized methyl silicone rubber; 20 parts of butyl rubber; 30 parts of modified filler; 10 parts of curing agent (specifically diethylaminomethyltriethoxysilane); 1 part of coupling agent (specifically silane coupling agent KH-560);
[0055] The modified filler is prepared by the following method:
[0056] (1) mixing attapulgite and wollastonite in a weight ratio of 2:1, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion; wherein the weight ratio of the total weight of the attapulgite and wollastonite to the weight of water is 1:10;
[0057] (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 40° C. for 3 h. After the stirring is completed, taking the solid and drying it to obtain a solid product 1; wherein the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and the dispersion is 6:1:2:600;
[0058] (3) The solid product 1 was calcined at 750° C. for 4 h to obtain a solid product 2, i.e., the modified filler.
[0059] Preparation method: room temperature vulcanized methyl silicone rubber, butyl rubber, modified filler, curing agent and coupling agent are uniformly mixed to obtain the composite adhesive.
[0060] Example 4 Preparation of composite adhesive
[0061] The raw materials are composed by weight: 40 parts of room temperature vulcanized methyl silicone rubber; 40 parts of butyl rubber; 50 parts of modified filler; 15 parts of curing agent (specifically diethylaminomethyltriethoxysilane); 5 parts of coupling agent (specifically silane coupling agent KH-560);
[0062] The modified filler is prepared by the following method:
[0063] (1) mixing attapulgite and wollastonite in a weight ratio of 4:1, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion; wherein the weight ratio of the total weight of the attapulgite and wollastonite to the weight of water is 1:8;
[0064] (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 60° C. for 1 hour. After the stirring is completed, taking the solid and drying it to obtain a solid product 1; wherein the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and the dispersion is 4:2:1:400;
[0065] (3) The solid product 1 is calcined at 800° C. for 2 h to obtain a solid product 2, i.e., the modified filler.
[0066] Preparation method: room temperature vulcanized methyl silicone rubber, butyl rubber, modified filler, curing agent and coupling agent are uniformly mixed to obtain the composite adhesive.
[0067] Example 5 Preparation of composite adhesive
[0068] The raw materials are composed by weight: 50 parts of room temperature vulcanized methyl silicone rubber; 30 parts of butyl rubber; 40 parts of modified filler; 12 parts of curing agent (specifically diethylaminomethyltriethoxysilane); 3 parts of coupling agent (specifically silane coupling agent KH-560);
[0069] The modified filler is prepared by the following method:
[0070] (1) mixing attapulgite and wollastonite in a weight ratio of 3:1, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion; wherein the weight ratio of the total weight of the attapulgite and wollastonite to the weight of water is 1:9;
[0071] (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 50° C. for 2 h. After the stirring is completed, taking the solid and drying it to obtain a solid product 1; wherein the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and the dispersion is 5:2:1:500;
[0072] (3) calcining the solid product 1 at 750° C. for 3 h to obtain a solid product 2;
[0073] (4) dispersing the solid product 2 in water, then adding the modifier, stirring at 70° C. for 2 h, separating the solid product, and drying to obtain the modified filler;
[0074] The weight ratio of the solid product 2, the modifier and the water in step (4) is 10:3:100; the modifier is selected from myristyl trimethyl ammonium chloride.
[0075] Preparation method: room temperature vulcanized methyl silicone rubber, butyl rubber, modified filler, curing agent and coupling agent are uniformly mixed to obtain the composite adhesive.
[0076] Example 6 Preparation of composite adhesive
[0077] The raw material composition by weight and the preparation method of Example 6 are the same as those of Example 5;
[0078] The difference is that the modifier used in step (4) of the modified filler preparation method is different; the modifier used in Example 6 is tetradecyl dimethyl benzyl ammonium chloride.
[0079] Example 7 Preparation of composite adhesive
[0080] The raw material composition by weight and the preparation method of Example 7 are the same as those of Example 5;
[0081] The difference is that the modifier used in step (4) of the modified filler preparation method is different; the modifier used in Example 7 is didecyl dimethyl ammonium chloride.
[0082] Example 8 Preparation of composite adhesive
[0083] The raw material composition by weight and the preparation method of Example 8 are the same as those of Example 5;
[0084] The difference is that the modifier used in step (4) of the modified filler preparation method is different; the modifier used in Example 8 is a mixed modifier composed of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride in a weight ratio of 1:1.
[0085] Example 9 Preparation of composite adhesive
[0086] The raw material composition by weight and the preparation method of Example 9 are the same as those of Example 5;
[0087] The difference is that the modifier used in step (4) of the modified filler preparation method is different; the modifier used in Example 8 is a mixed modifier composed of myristyltrimethylammonium chloride and didecyldimethylammonium chloride in a weight ratio of 1:1.
[0088] Example 10 Preparation of composite adhesive
[0089] The raw material composition by weight and the preparation method of Example 10 are the same as those of Example 5;
[0090] The difference is that the modifier used in step (4) of the modified filler preparation method is different; the modifier used in Example 8 is a mixed modifier composed of myristyltrimethylammonium chloride and tetradecyldimethylbenzylammonium chloride in a weight ratio of 1:1.
[0091] Experimental example
[0092] After the adhesives prepared in Examples 1 to 10 were cured at room temperature for 12 hours, their tensile strengths at -40°C were tested.
[0093] Tensile strength at -40℃(MPa) Composite adhesive prepared in Example 1 4.4 Composite adhesive prepared in Example 2 6.0 Composite adhesive prepared in Example 3 5.7 Composite adhesive prepared in Example 4 5.9 Composite adhesive prepared in Example 5 6.9 Composite adhesive prepared in Example 6 6.6 Composite adhesive prepared in Example 7 6.7 Composite adhesive prepared in Example 8 8.1 Composite adhesive prepared in Example 9 6.7 Composite adhesive prepared in Example 10 6.8
[0094] It can be seen from the experimental data in Table 1 that the composite adhesive prepared by the present invention still has good tensile strength under low temperature conditions of -40°C. Among them, the tensile strength of the composite adhesives prepared in Examples 2 to 4 at -40°C is significantly higher than that of the composite adhesive prepared in Example 1; this shows that the composite adhesive prepared by adding the modified filler obtained by modifying attapulgite and wollastonite by the method of the present invention to room temperature vulcanized methyl silicone rubber and butyl rubber can significantly improve the tensile strength of the composite adhesive at low temperature compared to the composite adhesive prepared by adding the unmodified filler composed of attapulgite and wollastonite.
[0095] It can be seen from the experimental data in Table 1 that the tensile strength of the composite adhesives prepared in Examples 5 to 7 at -40°C is further higher than that of the composite adhesive prepared in Example 2; this indicates that in the preparation process of the modified filler, the modified filler obtained by further modifying the solid product 2 by adding a modifier can further improve the tensile strength of the prepared composite adhesive at low temperatures.
[0096] It can be seen from the experimental data in Table 1 that the tensile strength of the composite adhesives prepared in Examples 5 to 7 at -40°C is improved compared with that of the composite adhesive prepared in Example 2, but the improvement is not large, and the improvement is much smaller than that of the composite adhesive prepared in Example 8; the composite adhesive prepared in Example 8 has very excellent tensile strength at -40°C; its tensile strength is much higher than that of the composite adhesives prepared in Examples 5 to 7. This shows that: in the preparation process of modified fillers, the selection of modifiers has an important influence on the tensile strength of the prepared composite adhesive at low temperature; when the modifier is selected from a composite modifier composed of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride, the tensile strength of the prepared composite adhesive at low temperature can be synergistically improved; the degree of improvement in the tensile strength of the prepared composite adhesive at low temperature is much higher than that of the composite adhesive prepared by the modifier selected from a single myristyl trimethyl ammonium chloride, tetradecyl dimethyl benzyl ammonium chloride or didecyl dimethyl ammonium chloride.
[0097] It can be seen from the experimental data in Table 1 that the tensile strength of the composite adhesives prepared in Examples 9 and 10 at -40°C is comparable to that of the composite adhesives prepared in Examples 5 to 7, and is also slightly improved compared to the tensile strength of the composite adhesive prepared in Example 2 at -40°C, and is much smaller than that of the composite adhesive prepared in Example 8; this shows that in the preparation process of the modified filler of the present invention, not all random combinations of modifiers can significantly improve the tensile strength of the prepared composite adhesive at low temperatures, and only the addition of a composite modifier composed of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride can further significantly improve the tensile strength of the prepared composite adhesive at low temperatures; however, the addition of other combinations of modifiers cannot further significantly improve the tensile strength of the prepared composite adhesive at low temperatures.
Claims
1. A composite adhesive, characterized in that: The raw material components include the following parts by weight: Room temperature vulcanized methyl silicone rubber 40-60 parts; butyl rubber 20-40 parts; filler 30-50 parts; curing agent 10-20 parts; coupling agent 1-5 parts; The filler is a modified filler; the modified filler is prepared by the following method: (1) mixing attapulgite and wollastonite, adding the mixture into water, and dispersing the mixture evenly to obtain a dispersion; (2) adding lanthanum chloride and magnesium chloride to the dispersion and stirring evenly; then adding sodium hydroxide and stirring at 40 to 60° C. for 1 to 3 hours. After the stirring is completed, the solid is taken out and dried to obtain a solid product 1; (3) calcining the solid product 1 at 700-800° C. for 2-4 h to obtain a solid product 2; (4) dispersing the solid product 2 in water, then adding a modifier, stirring at 60 to 90° C. for 1 to 3 hours, separating the solid product and drying it to obtain the modified filler; The modifier consists of tetradecyl dimethyl benzyl ammonium chloride and didecyl dimethyl ammonium chloride.
2. The composite adhesive according to claim 1, characterized in that: The raw material components include the following parts by weight: Room temperature vulcanized methyl silicone rubber 50-60 parts; butyl rubber 30-40 parts; filler 40-50 parts; curing agent 10-15 parts; coupling agent 1-3 parts.
3. The composite adhesive according to claim 1, characterized in that: The weight ratio of attapulgite to wollastonite is 2 to 4:
1.
4. The composite adhesive according to claim 3, characterized in that: The weight ratio of attapulgite to wollastonite is 3:
1.
5. The composite adhesive according to claim 1, characterized in that: The curing agent is selected from diethylaminomethyltriethoxysilane; The coupling agent is selected from silane coupling agent KH-560.
6. The composite adhesive according to claim 1, characterized in that: In step (1), the weight ratio of the total weight of attapulgite and wollastonite to water is 1:8-10.
7. The composite adhesive according to claim 6, characterized in that: In step (1), the weight ratio of the total weight of attapulgite and wollastonite to water is 1:
9.
8. The composite adhesive according to claim 1, characterized in that: In step (2), the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and dispersion liquid is 4-6:1-2:1-2:400-600.
9. The composite adhesive according to claim 1, characterized in that: In step (2), the weight ratio of lanthanum chloride, magnesium chloride, sodium hydroxide and dispersion is 5:2:1:
500.
10. Use of the composite adhesive according to any one of claims 1 to 9 in battery sealing or assembly.
Citation Information
Patent Citations
A graphene fire-retardant sealant
CN112226198B
Two-component hollow glass silicone sealant and preparation method thereof
CN103289635A
Modified butyl rubber sealing gasket material and preparation method thereof
CN103665602A